Children, citizenship and environment : #schoolstrike edition - Hayward, Bronwyn (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"When it was first published in 2012, Children, Citizenship and Environment correctly predicted a strong surge in youth activism as children are confronted by four difficult and intersecting challenges: dangerous environmental change, weakening democracies, growing social inequality, and a global economy marked by unprecedented youth unemployment and unsustainable resource extraction. Nearly a decade on, global school strikes in response to the threats of chaotic climate change have underscored why youth action is vital and effective. While the experience of a world pandemic may have interrupted the rise of youthful street activism, it has also served to underscore the problems of deepening inequality and the risks of increasingly authoritarian government responses which young citizens must also confront. Against this background the message of this substantially revised edition is as important today as it was when it was first published. Controversial yet ultimately hopeful, political scientist Bronwyn Hayward rethinks assumptions about youth citizenship in neoliberal democracies. Writing with co-authors: school climate strikers, indigenous and disability activists, teachers, researchers and community advocates, Hayward develops her 'SEEDS' model of ecological citizenship for a school strike generation. The SEEDS of citizenship focus on Social agency, Environmental education, Embedded justice, Decentred deliberation, Self-transcendence. Discussion considers how these SEEDS of citizenship support young citizens' democratic imagination and develop their 'handprint' for social justice. This groundbreaking book will be of interest to a wide audience, in particular teachers and professionals who work in Environmental Citizenship Education, as well as students and community activists with an interest in environmental change, democracy and intergenerational justice"--
OCLC-licensed vendor bibliographic record.
Keywords: Children and politics; Children and the environment; Citizenship -- Study and teaching; Democracy; BUSINESS & ECONOMICS / Development / Sustainable Development; NATURE / Ecology